Impact of a combination sound therapy on tinnitus distress: an exploratory one-year longitudinal study - Lelic, Dina; Caporali, Sueli; Parker, Daniel; Nielsen, Jakob; Balling, Laura Winther (Frontiers in Audiology and Otology, 2024)
Introduction Combination devices offering both amplification and sound therapy are commonly used in tinnitus management. However, there is insufficient evidence supporting the relationship between sound therapy and tinnitus outcomes. The aim of this study was to explore longitudinal effects of sound therapy on tinnitus-related distress using a combination device. Method Twenty participants with mild to moderate tinnitus related distress were fitted with combination devices that included three sound-therapy programs. The sound-therapy programs were selected by the participants from the available sounds offered in the combination device. The sounds comprised fractal music, nature sounds and combinations of the two. Participants were asked to wear the devices for 12 months and to complete questionnaires related to tinnitus distress at baseline and 1, 2, 4, 6, and 12 months after starting the treatment. Additionally, at 2, 4, 6, and 12 months, the device log data capturing information about amplification and sound-therapy use were collected. Results Tinnitus handicap inventory (THI), tinnitus functional index (TFI), tinnitus awareness and annoyance decreased following the device fitting. This improvement plateaued at 4 months. The degrees of improvement in THI, TFI and tinnitus annoyance were correlated with daily hours of sound-therapy use but not with daily hours of amplification-only or total device use. Conclusions A combination sound therapy consisting of therapy sounds, amplification as needed, and counseling was associated with a reduction in tinnitus-related distress. A future randomized controlled trial should be conducted to allow for detangling the effect of sound therapy from effects of amplification, counseling, placebo, and time itself, and to investigate the predictors of sound-therapy benefit and use.